Perbandingan Produksi Biogas BiodigesterBatchdan Kontinu pada Instalasi Biogas Kotoran Ternak - Rosurya Situmorang; I Putu Surya Wirawan; I Made Anom Sutrisna Wijaya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2024)
Biogas technology is an appropriate technology for treating livestock manure anaerobically by utilizingm ethanogenic bacteria to produce methane gas (CH4). Biogas uses renewable and flammable livestock manure raw materials with a clean methane (CH4) gas content and no black smoke. This study aims to obtain biogas production with the same length of fermentation time to obtain a comparison of batch and continuous biogas biodigester production in livestock manure biogas installations. The research began with a biodigester design using Microsoft paint and making a biodigester tool. The ratio of the combination of faeces and water is 1:1. The research was conducted in two trials, namely: a single batch biodigester containing 228 kg and a continuous batch of 228 kg with the addition of a mixture of raw materials once in three days of 18 kg. Both trials were observed every day using a U manometer to analyze batch and continuous biodigester biogas production. Based on the analysis of the specifications of the biodigester used, the capacity of the reactor tube is 0.254 m3, the raw material content capacity is 0.19 m3, the volume of the biogas chamber is 0.06 m3. The batch biodigester has a maximum pressure on day 25 of 104060.7 Pa with a production volume of biogas of 0.0616199 m3. The continuous system biodigester has a maximum pressure on day 25 of 105330.9 Pa with a production volume of biogas of 0.0623721 m3. Based on the trials, it was concluded that continuous biogas production produces higher pressure and volume of biogas than batches. The production of biogas once filled has the potential to produce more optimal biogas in a batch biodigester, while continuous biogas production will result in continued biogas production every day